(untitled) (Research, Society and Development, 2022)
This study aims to report the implementation of the culture circle in the school environment as a strategy for promoting the health of adolescents, with an emphasis on the problem of alcohol and other drug use. This is an experience report of extension actions developed by nursing students in the project “Prevention of drug use in the school environment: an approach with educators and students from public schools”. The activities were carried out between January and June 2019, with the participation of 33 adolescents from a public high school, located in the city of Crato, Ceará, Brazil. The experience of culture circles in the school environment established a dialogue between students and adolescents based on active listening and the exchange of experiences in a pleasant way. The method promoted the critical-reflective process on the use of alcohol and other drugs, learning and awareness, autonomy for expression, participation and questioning of reality, enabling adolescents to act in the best care of their health, encouraging the development of healthy and the leading role in the health process.